2002
DOI: 10.1128/mcb.22.6.1626-1638.2002
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Cofactor Recruitment by Orphan Receptor Hepatocyte Nuclear Factor 4α1: Modulation by the F Domain

Abstract: For most ligand-dependent nuclear receptors, the status of endogenous ligand modulates the relative affinities for corepressor and coactivator complexes. It is less clear what parameters modulate the switch between corepressor and coactivator for the orphan receptors. Our previous work demonstrated that hepatocyte nuclear factor 4␣1 (HNF4␣1, NR2A1) interacts with the p160 coactivator GRIP1 and the cointegrators CBP and p300 in the absence of exogenously added ligand and that removal of the F domain enhances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 77 publications
(91 reference statements)
4
86
0
5
Order By: Relevance
“…p160 proteins typically link other coactivators to the transcription initiation complex, whereas CBP/p300 can directly acetylate histones and/or other components of the transcription initiation complex (47). Similarly, orphan receptor HNF-4a was shown to interact with CBP/ p300 and GRIP-1 (48,49). In line with these studies, we found that CBP and GRIP-1 were associated with HNF-4a at the proximal vegf-D promoter (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…p160 proteins typically link other coactivators to the transcription initiation complex, whereas CBP/p300 can directly acetylate histones and/or other components of the transcription initiation complex (47). Similarly, orphan receptor HNF-4a was shown to interact with CBP/ p300 and GRIP-1 (48,49). In line with these studies, we found that CBP and GRIP-1 were associated with HNF-4a at the proximal vegf-D promoter (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, whereas studies using truncated mutants assume that N-terminal deletion of the DNA binding domain or Cterminal deletion of the F-domain have no effect on ligand binding to HNF-4␣, the validity of these assumptions has never been demonstrated. The latter is especially surprising, since the C-terminal F-domain is a well recognized negative regula- tor of HNF-4␣ transactivation and is thought to directly interact with the ligand binding domain E (8,16,22,38). Since high affinity ligand binding and ligand-induced conformational changes are hallmarks of ligand-dependent nuclear receptors, fluorescence binding assays and circular dichroism were used in the present study to directly address these issues by examining ligand specificity and conformational responsiveness to ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of HNF-4␣ over a decade ago (1), there has been considerable controversy regarding whether this orphan nuclear transcription factor is (8,11,14,19) or is not (12,16,18) ligand-activated. Due to problems with crystallizing the full-length HNF-4␣ (aa 1-455) or HNF-4␣ mutants containing an intact C-terminal F-domain (17,18), almost nothing is known regarding the ligand specificity, structure, or conformational dependence of the full-length HNF-4␣ (aa 1-455).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations